Enhanced water-based chromium-free zinc-aluminum coating as well as preparation method and application thereof
By combining polydopamine-modified nanosilicon dioxide with sheet-shaped zinc-aluminum alloy powder in aqueous chromium-free zinc-aluminum coating, the problem of insufficient coating hardness, wear resistance and corrosion resistance is solved, and better performance and longer service life are achieved.
Patent Information
- Application Number
- CN202411761859.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The existing water-based chromium-free zinc-aluminum coatings have problems of insufficient hardness, wear resistance and corrosion resistance in actual applications, which are difficult to meet the severe natural environment and environmental protection requirements.
Polydopamine modified nanosilica is combined with sheet-shaped zinc-aluminum alloy powder, and the dispersion, hardness and corrosion resistance of the coating are improved through the adhesion and chelation reaction of the modified nanomaterials.
It significantly improves the hardness, wear resistance and corrosion resistance of the coating, enhances the density and adhesion of the coating, and extends the service life of the coating.
Smart Images

Figure CN119570361A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corrosion coatings, and relates to an enhanced water-based chromium-free zinc-aluminum coating, a preparation method and applications thereof, and specifically relates to a polydopamine-modified nano-silicon dioxide-enhanced water-based chromium-free zinc-aluminum coating, a preparation method and applications thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Power fittings play a role in fixing and supporting the connection between conductors and transmission towers, and conductors and insulators in high-voltage transmission lines. Since they are mostly exposed to the elements, they are bound to encounter corrosion problems. Corrosion failure of fittings will cause line disconnection or insulator disconnection, seriously affecting the safety of the power grid. Therefore, it is crucial to adopt effective anti-corrosion protection measures. At present, the most commonly used method for anti-corrosion of power fittings is hot-dip galvanizing, but this method has serious pollution in the production process, and the resulting coating is thin and uneven in thickness. The protection effect is insufficient in outdoor environments, and the actual service life in heavy corrosion areas is far from meeting the requirements.
[0004] The anti-rust effect of zinc-aluminum coating is more than 7 times that of traditional galvanizing. It is widely used due to its excellent anti-corrosion performance. 6+ The presence of chromium causes environmental pollution and potential carcinogenic factors. Therefore, a composite reagent with bonding and corrosion inhibition effect is used to replace the chromic anhydride in the zinc-aluminum coating to prepare an environmentally friendly and corrosion-resistant water-based chromium-free zinc-aluminum coating, and it is applied to the protection of power fittings, which will have a positive significance for the safe operation of the power grid.
[0005] However, there are still some defects in the research of water-based chromium-free zinc-aluminum coatings. Under actual application conditions, the coatings have the defects of poor hardness, poor wear resistance and inferior corrosion resistance to zinc-aluminum coatings. Therefore, under the environmental protection requirements of various countries and more severe natural use conditions, it has become a current need to further improve the corrosion resistance and wear resistance of chromium-free zinc-aluminum coatings and develop chromium-free zinc-aluminum coatings with better performance. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide an enhanced water-based chromium-free zinc-aluminum coating, a preparation method and application thereof.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In a first aspect, the present invention provides an enhanced water-based chromium-free zinc-aluminum coating, comprising a component A and a component B. When used, the component A and the component B are mixed evenly, wherein:
[0009] The component A comprises the following raw materials, by weight: 10-20 parts of silane binder, 1-4 parts of corrosion inhibitor, and 20-80 parts of solvent;
[0010] The component B comprises the following raw materials, by mass: 30-60 parts of flaky zinc-aluminum alloy powder, 10-20 parts of silane binder, 1-3 parts of polydopamine-modified nano-silicon dioxide, and 17-32 parts of auxiliary agent.
[0011] Inorganic nanofillers have been widely used in composite coatings in recent years due to their good mechanical properties and chemical stability. Well-dispersed nano inorganic fillers can greatly enhance the mechanical properties of water-based coatings. Among the many inorganic nanofillers, nano silicon dioxide has good electrical insulation, chemical corrosion resistance and excellent thermodynamic properties. Adding nano silicon dioxide to Dacro coatings and utilizing some unique properties of nanoparticles can improve the hardness, scratch resistance, friction reduction and corrosion resistance of the coating, while maintaining the advantages of the coating itself. However, due to the different surface properties of inorganic nanoparticles such as silicon dioxide and polymers, their compatibility is poor, and inorganic nanoparticles such as silicon dioxide are affected by van der Waals forces and have strong affinity with each other, they are prone to agglomeration and sedimentation in the dispersion medium, affecting the density, adhesion and corrosion resistance of the coating.
[0012] The present invention adds polydopamine to the water-based chromium-free zinc-aluminum coating, and polydopamine has super strong adhesion, biocompatibility and hydrophilicity to nanomaterials. The surface of polydopamine has abundant functional groups (such as catechol, amine and imine), which can provide more active sites for covalent modification with nano-silica. The material modified by polydopamine can be secondary modified by physical action (hydrogen bond, coordination action, etc.) or chemical reaction.
[0013] The surface functional groups of polydopamine can also react with the corrosion products of the filler flaky zinc-aluminum alloy metal powder and the metal substrate to form a protective layer, effectively preventing the migration of corrosion ions in the corrosion system and improving the corrosion resistance of the coating. Therefore, polydopamine-modified nano-silica improves the dispersibility of nano-silica while also reacting with metal ions to chelate and synergistically improve the anti-corrosion performance of the coating.
[0014] The modified coating prepared by modifying the nanomaterial with polydopamine can make the nanomaterial have better dispersibility and improve the physical and chemical properties of the coating, especially the wear resistance and heat resistance.
[0015] In some embodiments, the corrosion inhibitor is benzotriazole, 8-hydroxyquinoline or polyaspartic acid.
[0016] In some embodiments, the silane adhesive is AC-66 or AC-66E.
[0017] In some embodiments, the auxiliary agent is a wetting and dispersing agent, a protective agent or a defoaming agent.
[0018] Preferably, the wetting and dispersing agent is VXW 6208 or Tween-20;
[0019] The protective agent is polyethylene glycol-400 or ethylene glycol;
[0020] The defoaming agent is Dow Corning DC-65, BYK-092 or BYK-1781.
[0021] In some embodiments, the solvent is an ethanol aqueous solution, and the mass ratio of ethanol to water in the solvent is 1:1.2-3. Silane coupling agent hydrolyzes in aqueous solution to generate corresponding silanols, which are usually very unstable. The hydrolysis product silanol molecules are easy to condense with each other to form siloxane Si-O-Si. If the condensation reaction rate in the system is greater than the hydrolysis reaction, a large amount of silanols condense into siloxane polymers, which will lead to a decrease in solution concentration and reduce the stability of the coating. Therefore, in order to improve the stability of the silane coupling agent in water, adding an appropriate amount of ethanol is conducive to the stability of the aqueous solution.
[0022] In some embodiments, the particle size of the flaky zinc-aluminum alloy powder is 9-15 μm.
[0023] Preferably, in the flaky zinc-aluminum alloy powder, the mass ratio of aluminum powder to zinc powder is 1:4-10.
[0024] In a second aspect, the present invention provides a method for preparing the enhanced water-based chromium-free zinc-aluminum coating, comprising the following steps:
[0025] Add the corrosion inhibitor to the ethanol aqueous solution, stir to dissolve, then add the silane binder, stir and hydrolyze for 30-60 minutes to obtain component A;
[0026] After the silane binder and the auxiliary agent are mixed, the flaky zinc-aluminum alloy powder is added, and after mixing, the polydopamine-modified nano-silicon dioxide is added to obtain the B component.
[0027] The coating is prepared by mixing component A and component B of the coating under stirring, ultrasonically dispersing, and then stirring for a set time.
[0028] In some embodiments, the preparation method of the polydopamine-modified nano-silica is: adding nano-silica to a Tris buffer solution, and ultrasonically dispersing to obtain a nano-silica dispersion;
[0029] Under stirring conditions, add the dopamine hydrochloride solution to the nano-silicon dioxide dispersion and continue stirring for 12-24 hours;
[0030] After the reaction system is solid-liquid separated, the solid is washed, dried and ground to obtain polydopamine-modified nano-silicon dioxide.
[0031] Dopamine undergoes self-polymerization under weak alkaline conditions to generate polydopamine, and Tris buffer can be used as a weak alkaline environment to regulate the self-polymerization of dopamine hydrochloride, and the pH value of the buffer environment is about 8.5. The method of modifying nanomaterials with polydopamine is relatively simple. Dopamine can form polydopamine on the surface of nanomaterials through self-polymerization reaction at room temperature under weak alkaline conditions.
[0032] Preferably, the mass ratio of nano-silicon dioxide to dopamine hydrochloride is 2.5-25:1.
[0033] Preferably, the concentration of the Tris buffer solution is 0.01 mol / L and the pH value is 8.5.
[0034] Preferably, the washing is to repeatedly wash the product with anhydrous ethanol and deionized water until the supernatant becomes clear.
[0035] Preferably, the drying is vacuum drying, the vacuum drying temperature is 55-65° C., and the vacuum drying time is 12-24 h.
[0036] In some embodiments, the ultrasonic dispersion time is 3-10 min.
[0037] In some embodiments, the stirring is magnetic stirring, and the magnetic stirring time is 3-6 hours.
[0038] In a third aspect, the present invention provides a method for preparing an enhanced water-based chromium-free zinc-aluminum coating, comprising the following steps:
[0039] Grind the surface of the workpiece to be protected to make it rough, clean it, and dry it;
[0040] Spray the coating on the treated workpiece surface, then keep the workpiece at 70-80℃ for 20-30min, then program the temperature to 260-300℃ and keep it for 20-30min;
[0041] After the workpiece is cooled, a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica is obtained.
[0042] In some embodiments, the workpiece is made of steel.
[0043] In some embodiments, the surface of the workpiece is roughened with sandpaper slurry and then cleaned with anhydrous ethanol.
[0044] In some embodiments, the water-based chromium-free zinc-aluminum coating has a thickness of 12-20 μm.
[0045] In a fourth aspect, the present invention provides the use of the enhanced water-based chromium-free zinc-aluminum coating in the preparation of anti-corrosion coatings for electric power fittings.
[0046] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0047] 1. The present invention adopts polydopamine to modify nano-silica. Polydopamine contains rich functional group structures and has good interface bonding ability with various materials. It can enhance the dispersibility of nano-silica in the solution and improve the hardness and wear resistance of the coating.
[0048] 2. The polydopamine used in the present invention has strong adhesion and can be adsorbed on the metal surface. 2+ There is a chelating effect between them, which can inhibit the corrosion of metals to a certain extent.
[0049] 3. The preparation process of the nano-silica modified by polydopamine in the present invention is simple, the reaction conditions are mild, it is green and environmentally friendly, the cost is low, and the anti-corrosion performance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0051] Figure 1 This is a magnifying glass photograph of the coating prepared in Example 1 of the present invention;
[0052] Figure 2 This is a magnifying glass photograph of the coating prepared in Example 2 of the present invention;
[0053] Figure 3 This is a magnifying glass photograph of the coating prepared in Comparative Example 2 of the present invention;
[0054] Figure 4 This is a photo of the adhesion of the coating prepared in Example 1 of the present invention;
[0055] Figure 5 This is a photo of the adhesion of the coating prepared in Example 2 of the present invention;
[0056] Figure 6 This is a photo of the adhesion of the coating prepared in Comparative Example 2 of the present invention;
[0057] Figure 7 This is a photo of the salt water resistance of the coating prepared in Example 1 of the present invention after 800 hours;
[0058] Figure 8 This is a photo of the salt water resistance of the coating prepared in Example 2 of the present invention after 800 hours;
[0059] Fig. 9 This is a photo of the salt water resistance of the coating prepared in Comparative Example 2 of the present invention after 500 hours. DETAILED DESCRIPTION
[0060] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0061] The present invention will be further described below in conjunction with the embodiments.
[0062] Example 1
[0063] Preparation of polydopamine modified nano-silica: Add 0.6g of nano-silica to 200mL of Tris buffer solution with a concentration of 0.01mol / L, and ultrasonically disperse for 30min to obtain a nano-silica dispersion. Dissolve 0.24g of dopamine hydrochloride in 10mL of deionized water and stir to dissolve. Add the dopamine hydrochloride solution to the nano-silica dispersion under magnetic stirring and stir magnetically for 12h. Wash the reacted material repeatedly with anhydrous ethanol and deionized water until the supernatant becomes clear, vacuum dry at 60°C for 12h, and grind to obtain polydopamine modified nano-silica.
[0064] Component A: 10g silane binder AC-66, 1g corrosion inhibitor benzotriazole, 9g ethanol, 11g deionized water;
[0065] Component B: 30g flaky zinc-aluminum alloy powder (the mass ratio of aluminum powder to zinc powder is 1:5, and the particle size is 15μm), 10g silane binder AC-66, 1g polydopamine-modified nano-silica, 16g protective agent polyethylene glycol-400, 1g wetting and dispersing agent VXW6208, and 1g defoaming agent Dow Corning DC-65.
[0066] The preparation method is as follows:
[0067] (1) adding benzotriazole to the prepared alcohol aqueous solution and stirring to dissolve, then adding a silane binder, and hydrolyzing for 30 minutes under magnetic stirring to obtain a silane hydrolyzate of component A;
[0068] (2) mixing the silane binder and the auxiliary agent uniformly, adding the flaky zinc-aluminum alloy powder, stirring uniformly with a magnetic force, and then adding the prepared polydopamine-modified nano-silica to obtain component B;
[0069] (3) adding component A to the metal powder slurry of component B in a stirring state, stirring evenly, ultrasonically dispersing for 3 minutes, and then magnetically stirring for 3 hours to obtain a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica;
[0070] (4) The surface of the Q235 carbon steel plate was roughened with sandpaper, and the surface oil was cleaned with anhydrous ethanol and dried for later use;
[0071] (5) adding the prepared coating to a spray gun and spraying it on the treated carbon steel plate surface, and controlling the coating thickness by controlling the coating spraying amount;
[0072] (6) The sprayed carbon steel plate was placed in a box furnace and kept at 70°C for 20 minutes, then the temperature was raised to 260°C and kept for 30 minutes. After natural cooling, a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica was obtained.
[0073] In this embodiment, the thickness of the water-based chromium-free zinc-aluminum coating enhanced by polydopamine-modified nano-silicon dioxide is about 15 μm.
[0074] Example 2
[0075] Preparation of polydopamine modified nano-silica: Add 0.6g of nano-silica to 200mL of Tris buffer solution with a concentration of 0.01mol / L, and ultrasonically disperse for 30min to obtain a nano-silica dispersion. Dissolve 0.24g of dopamine hydrochloride in 10mL of deionized water and stir to dissolve. Add the dopamine hydrochloride solution to the nano-silica dispersion under magnetic stirring and stir magnetically for 12h. Wash the reacted material repeatedly with anhydrous ethanol and deionized water until the supernatant becomes clear, vacuum dry at 60°C for 12h, and grind to obtain polydopamine modified nano-silica.
[0076] Component A: 12g silane binder AC-66, 1g corrosion inhibitor benzotriazole, 10g ethanol, 20g deionized water;
[0077] Component B: 30g flaky zinc-aluminum alloy powder (the mass ratio of aluminum powder to zinc powder is 1:5, and the particle size is 15μm), 12g silane binder AC-66, 1.5g polydopamine-modified nano-silica, 19g protective agent polyethylene glycol-400, 1.5g wetting and dispersing agent VXW6208, and 1.5g defoaming agent Dow Corning DC-65.
[0078] The preparation method is as follows:
[0079] (1) adding benzotriazole to the prepared alcohol aqueous solution and stirring to dissolve, then adding a silane binder, and hydrolyzing for 30 minutes under magnetic stirring to obtain a silane hydrolyzate of component A;
[0080] (2) mixing the silane binder and the auxiliary agent uniformly, adding the flaky zinc-aluminum alloy powder, stirring uniformly with a magnetic force, and then adding the prepared polydopamine-modified nano-silica to obtain component B;
[0081] (3) adding component A to the metal powder slurry of component B in a stirring state, stirring evenly, ultrasonically dispersing for 5 minutes, and then magnetically stirring for 3 hours to obtain a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica;
[0082] (4) The surface of the Q235 carbon steel plate was roughened with sandpaper, and the surface oil was cleaned with anhydrous ethanol and dried for later use;
[0083] (5) adding the prepared coating to a spray gun and spraying it on the treated carbon steel plate surface, and controlling the coating thickness by controlling the coating spraying amount;
[0084] (6) The sprayed carbon steel plate was placed in a box furnace and kept at 70°C for 20 minutes, then the temperature was raised to 270°C and kept for 30 minutes. After natural cooling, a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica was obtained.
[0085] In this embodiment, the thickness of the water-based chromium-free zinc-aluminum coating enhanced by polydopamine-modified nano-silicon dioxide is about 15 μm.
[0086] Example 3
[0087] Preparation of polydopamine modified nano-silica: Add 0.6g of nano-silica to 200mL of Tris buffer solution with a concentration of 0.01mol / L, and ultrasonically disperse for 30min to obtain a nano-silica dispersion. Dissolve 0.24g of dopamine hydrochloride in 10mL of deionized water and stir to dissolve. Add the dopamine hydrochloride solution to the nano-silica dispersion under magnetic stirring and stir magnetically for 12h. Wash the reacted material repeatedly with anhydrous ethanol and deionized water until the supernatant becomes clear, vacuum dry at 60°C for 12h, and grind to obtain polydopamine modified nano-silica.
[0088] Component A: 14g silane binder AC-66, 2g corrosion inhibitor 8-hydroxyquinoline, 14g ethanol, 26g deionized water;
[0089] Component B: 40g flaky zinc-aluminum alloy powder (the mass ratio of aluminum powder to zinc powder is 1:5, and the particle size is 15μm), 14g silane binder AC-66, 2g polydopamine-modified nano-silica, 22g protective agent polyethylene glycol-400, 2g wetting and dispersing agent VXW6208, and 22g defoaming agent BYK-09.
[0090] The preparation method is as follows:
[0091] (1) adding 8-hydroxyquinoline to the prepared alcohol aqueous solution and stirring to dissolve, then adding a silane binder, and hydrolyzing for 40 minutes under magnetic stirring to obtain a silane hydrolyzate of component A;
[0092] (2) mixing the silane binder and the auxiliary agent uniformly, adding the flaky zinc-aluminum alloy powder, stirring uniformly with a magnetic force, and then adding the prepared polydopamine-modified nano-silica to obtain component B;
[0093] (3) adding component A to the metal powder slurry of component B in a stirring state, stirring evenly, ultrasonically dispersing for 7 minutes, and then magnetically stirring for 4 hours to obtain a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica;
[0094] (4) The surface of the Q235 carbon steel plate was roughened with sandpaper, and the surface oil was cleaned with anhydrous ethanol and dried for later use;
[0095] (5) adding the prepared coating to a spray gun and spraying it on the treated carbon steel plate surface, and controlling the coating thickness by controlling the coating spraying amount;
[0096] (6) The sprayed carbon steel plate was placed in a box furnace and kept at 80°C for 30 minutes, then the temperature was raised to 270°C and kept for 20-30 minutes. After natural cooling, a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica was obtained.
[0097] In this embodiment, the thickness of the water-based chromium-free zinc-aluminum coating enhanced by polydopamine-modified nano-silicon dioxide is about 16 μm.
[0098] Example 4
[0099] Preparation of polydopamine modified nano-silica: Add 1g of nano-silica to 200mL of Tris buffer solution with a concentration of 0.01mol / L, and ultrasonically disperse for 60min to obtain a nano-silica dispersion. Dissolve 0.24g of dopamine hydrochloride in 10mL of deionized water and stir to dissolve. Add the dopamine hydrochloride solution to the nano-silica dispersion under magnetic stirring and stir magnetically for 24h. Wash the reacted material repeatedly with anhydrous ethanol and deionized water until the supernatant becomes clear, vacuum dry at 60°C for 24h, and grind to obtain polydopamine modified nano-silica.
[0100] Component A: 16g silane binder AC-66E, 3g corrosion inhibitor polyaspartic acid, 20g ethanol, 40g deionized water;
[0101] Component B: 50g flaky zinc-aluminum alloy powder (the mass ratio of aluminum powder to zinc powder is 1:5, and the particle size is 15μm), 16g silane binder AC-66, 2.5g polydopamine-modified nano-silica, 26g protective agent ethylene glycol, 2g wetting and dispersing agent Tween-20, and 2g defoaming agent BYK-092.
[0102] The preparation method is as follows:
[0103] (1) adding polyaspartic acid to the prepared alcohol aqueous solution and stirring to dissolve, then adding a silane binder, and hydrolyzing for 50 minutes under magnetic stirring to obtain a silane hydrolyzate of component A;
[0104] (2) mixing the silane binder and the auxiliary agent uniformly, adding the flaky zinc-aluminum alloy powder, stirring uniformly with a magnetic force, and then adding the prepared polydopamine-modified nano-silica to obtain component B;
[0105] (3) adding component A to the metal powder slurry of component B in a stirring state, stirring evenly, ultrasonically dispersing for 9 minutes, and then magnetically stirring for 5 hours to obtain a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica;
[0106] (4) The surface of the Q235 carbon steel plate was roughened with sandpaper, and the surface oil was cleaned with anhydrous ethanol and dried for later use;
[0107] (5) adding the prepared coating to a spray gun and spraying it on the treated carbon steel plate surface, and controlling the coating thickness by controlling the coating spraying amount;
[0108] (6) The sprayed carbon steel plate was placed in a box furnace and kept at 80°C for 30 minutes, then the temperature was raised to 300°C and kept for 20 minutes. After natural cooling, a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica was obtained.
[0109] In this embodiment, the thickness of the water-based chromium-free zinc-aluminum coating enhanced by polydopamine-modified nano-silicon dioxide is about 15 μm.
[0110] Example 5
[0111] Preparation of polydopamine modified nano-silica: Add 1g of nano-silica to 200mL of Tris buffer solution with a concentration of 0.01mol / L, and ultrasonically disperse for 60min to obtain a nano-silica dispersion. Dissolve 0.24g of dopamine hydrochloride in 10mL of deionized water and stir to dissolve. Add the dopamine hydrochloride solution to the nano-silica dispersion under magnetic stirring and stir magnetically for 24h. Wash the reacted material repeatedly with anhydrous ethanol and deionized water until the supernatant becomes clear, vacuum dry at 60°C for 24h, and grind to obtain polydopamine modified nano-silica.
[0112] Component A: 20g silane binder AC-66E, 4g corrosion inhibitor polyaspartic acid, 20g ethanol, 60g deionized water;
[0113] Component B: 60g of flaky zinc-aluminum alloy powder (the mass ratio of aluminum powder to zinc powder is 1:5, and the particle size is 15μm), 20g of silane binder AC-66, 3g of polydopamine-modified nano-silica, 28g of protective agent ethylene glycol, 2g of wetting and dispersing agent Tween-20, and 2g of defoaming agent BYK-1781.
[0114] The preparation method is as follows:
[0115] (1) adding polyaspartic acid to the prepared alcohol aqueous solution and stirring to dissolve, then adding a silane binder, and hydrolyzing for 60 minutes under magnetic stirring to obtain a silane hydrolyzate of component A;
[0116] (2) mixing the silane binder and the auxiliary agent uniformly, adding the flaky zinc-aluminum alloy powder, stirring uniformly with a magnetic force, and then adding the prepared polydopamine-modified nano-silica to obtain component B;
[0117] (3) adding component A to the metal powder slurry of component B in a stirring state, stirring evenly, ultrasonically dispersing for 10 minutes, and then magnetically stirring for 6 hours to obtain a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica;
[0118] (4) The surface of the Q235 carbon steel plate was roughened with sandpaper, and the surface oil was cleaned with anhydrous ethanol and dried for later use;
[0119] (5) adding the prepared coating to a spray gun and spraying it on the treated carbon steel plate surface, and controlling the coating thickness by controlling the coating spraying amount;
[0120] (6) The sprayed carbon steel plate was placed in a box furnace and kept at 80°C for 30 minutes, then the temperature was raised to 300°C and kept for 20 minutes. After natural cooling, a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica was obtained.
[0121] In this embodiment, the thickness of the water-based chromium-free zinc-aluminum coating enhanced by polydopamine-modified nano-silicon dioxide is about 16 μm.
[0122] Comparative Example 1
[0123] The difference from Example 1 is that the addition of polydopamine-modified nano-silica is omitted, and other parameters and steps are the same as those in Example 1.
[0124] Comparative Example 2
[0125] The difference from Example 1 is that the polydopamine-modified nano-silica is replaced by nano-silica, and the other parameters and steps are the same as those in Example 1.
[0126] The coatings prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests. The coating thickness test was based on standard GB / T13452.2-2008 "Determination of film thickness of paints and varnishes"; the adhesion test was based on standard GB / T 9286-2021 "Scratch test for paints and varnishes"; the salt water resistance test was based on standard GB / T 9274-1988 "Determination of resistance of paints and varnishes to liquid media"; the neutral salt spray resistance test was based on GB / T 10125-2021 "Artificial atmosphere corrosion test salt spray test".
[0127] The test results of the coating properties prepared in Examples 1-5 of the present invention and Comparative Examples 1-2 are shown in the following table:
[0128] Table 1
[0129]
[0130] It can be seen from the table that the thickness of the prepared coating is uniform; the adhesion of the coatings prepared in Examples 1-5 is all level 1, while the adhesion of the coatings prepared in Comparative Examples 1-2 is level 2. Figure 4 , 5 It can also be directly seen from the adhesion photos of the coatings prepared by Examples 1 and 2 that the coatings prepared by Examples 1 and 2 have excellent adhesion, while the nano-silica coating prepared in Comparative Example 2 that has not been modified with polydopamine has poor adhesion. This may be because the coating prepared by adding polydopamine-modified nano-silica has strong adhesion on the surface of the substrate, while adding a single nano-silica is prone to form agglomerates, which is prone to stress concentration around it, causing defects in the coating, resulting in a decrease in the hardness and impact resistance of the coating, thereby reducing the adhesion on the surface of the substrate.
[0131] from Figure 1 and 2 It can be seen that the surfaces of the coatings prepared in Examples 1 and 2 are more uniform, without obvious agglomerated particles, while the coating prepared in Comparative Example 2 clearly has more particles, which may be the agglomeration of filler particles produced by the agglomeration of nano-silicon dioxide, which causes the coating to adhere unevenly to the surface of the substrate and has poor adhesion.
[0132] The salt water resistance of the coatings prepared in Examples 1-5 is about 800h, while the salt water resistance of the coatings prepared in Comparative Examples 1-2 is 400-500h. Figure 7 , Figure 8 , Fig. 9 The salt water resistance performance of the prepared coating can also be directly seen from the photos. The coatings prepared in Examples 1 and 2 were immersed in 10% salt water by mass, of which 2 / 3 of the coatings were immersed in salt water. After 800 hours of salt water immersion, it can be seen that the coatings did not show obvious large-area pitting ( Figure 7 , 8), indicating that polydopamine modified nano-silica improves the dispersibility of silica in the coating, making the coating more uniform and dense. At the same time, polydopamine will also interact with Fe 2+ Chelation occurs, further improving the corrosion resistance of the coating.
[0133] However, the coating prepared in Comparative Example 2 showed large-area rust after being immersed in salt water for 500 hours ( Fig. 9 ) is due to the presence of nano-silicon dioxide agglomerated particles in the prepared coating, which makes the formed coating uneven, poorly dense, and poorly bonded to the substrate surface. The corrosive medium is more likely to enter the interior through the coating defects and corrode the substrate.
[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An enhanced water-based chromium-free zinc-aluminum coating, characterized in that: It includes component A and component B. When used, component A and component B are mixed evenly, wherein: The component A comprises the following raw materials, by weight: 10-20 parts of silane binder, 1-4 parts of corrosion inhibitor, and 20-80 parts of solvent; The component B comprises the following raw materials, by mass: 30-60 parts of flaky zinc-aluminum alloy powder, 10-20 parts of silane binder, 1-3 parts of polydopamine-modified nano-silicon dioxide, and 17-32 parts of auxiliary agent.
2. The enhanced water-based chromium-free zinc-aluminum coating according to claim 1, characterized in that: The corrosion inhibitor is benzotriazole, 8-hydroxyquinoline or polyaspartic acid; Or, the silane adhesive is AC-66 or AC-66E; Or, the auxiliary agent is a wetting and dispersing agent, a protective agent or a defoaming agent; Or, the wetting and dispersing agent is VXW 6208 or Tween-20; The protective agent is polyethylene glycol-400 or ethylene glycol; The defoaming agent is Dow Corning DC-65, BYK-092 or BYK-1781.
3. The enhanced water-based chromium-free zinc-aluminum coating according to claim 1, characterized in that: The solvent is an ethanol aqueous solution, and the mass ratio of ethanol to water in the solvent is 1:1.2-3.
4. The enhanced water-based chromium-free zinc-aluminum coating according to claim 1, characterized in that: The particle size of the flaky zinc-aluminum alloy powder is 9-15 μm; Preferably, in the flaky zinc-aluminum alloy powder, the mass ratio of aluminum powder to zinc powder is 1:4-10.
5. The method for preparing the enhanced water-based chromium-free zinc-aluminum coating according to any one of claims 1 to 4, characterized in that: The steps include: Add the corrosion inhibitor to the ethanol aqueous solution, stir to dissolve, then add the silane binder, stir and hydrolyze for 30-60 minutes to obtain component A; After the silane binder and the auxiliary agent are mixed, the flaky zinc-aluminum alloy powder is added, and after mixing, the polydopamine-modified nano-silicon dioxide is added to obtain the B component. The coating is prepared by mixing component A and component B of the coating under stirring, ultrasonically dispersing, and then stirring for a set time.
6. The method for preparing the enhanced water-based chromium-free zinc-aluminum coating according to claim 5, characterized in that: The preparation method of the polydopamine-modified nano-silicon dioxide is as follows: adding the nano-silicon dioxide into a Tris buffer solution and performing ultrasonic dispersion to obtain a nano-silicon dioxide dispersion; Under stirring conditions, add the dopamine hydrochloride solution to the nano-silicon dioxide dispersion and continue stirring for 12-24 hours; After the reaction system is solid-liquid separated, the solid is washed, dried and ground to obtain polydopamine-modified nano-silicon dioxide; Preferably, the mass ratio of nano-silicon dioxide to dopamine hydrochloride is 2.5-25:1; Preferably, the concentration of the Tris buffer solution is 0.01 mol / L and the pH value is 8.5; Preferably, the washing is to repeatedly wash the product with anhydrous ethanol and deionized water until the supernatant becomes clear; Preferably, the drying is vacuum drying, the vacuum drying temperature is 55-65° C., and the vacuum drying time is 12-24 h.
7. The method for preparing the enhanced water-based chromium-free zinc-aluminum coating according to claim 5, characterized in that: The ultrasonic dispersion time is 3-10min; Preferably, the stirring is magnetic stirring, and the time of magnetic stirring is 3-6 hours.
8. A method for preparing an enhanced water-based chromium-free zinc-aluminum coating, characterized in that: The steps include: Grind the surface of the workpiece to be protected to make it rough, clean it, and dry it; Spraying the enhanced water-based chromium-free zinc-aluminum coating according to any one of claims 1 to 4 onto the treated surface of the workpiece, then keeping the workpiece at 70-80° C. for 20-30 minutes, then raising the temperature to 260-300° C. and keeping it for 20-30 minutes; After the workpiece is cooled, a water-based chromium-free zinc-aluminum coating reinforced with polydopamine-modified nano-silica is obtained.
9. The method for preparing the enhanced water-based chromium-free zinc-aluminum coating according to claim 7, characterized in that: The workpiece surface was roughened with sandpaper slurry and then cleaned with anhydrous ethanol; Preferably, the thickness of the water-based chromium-free zinc-aluminum coating is 12-20 μm.
10. Use of the enhanced water-based chromium-free zinc-aluminum coating according to any one of claims 1 to 4 in the preparation of anti-corrosion coatings for electric power fittings.
Citation Information
Patent Citations
Aqueous composite zinc-aluminum anticorrosion coating
CN107964351A
Nano silicon dioxide modified flame-retardant coating and preparation method thereof
CN117210096A